Analysis Of Workload On Employee Performance In The Front Office Department At The Apurva Kempinski Bali - Putradewa Yo, Komang Bagus; Winia, I Nyoman; Sagitarini, Luh Linna (Jurnal Sains Terapan Pariwisata, 2022)
Purpose: This study aims to determine whether or not there is and how much influence workload has on employee performance at the Front Office Department at The Apurva Kempinski Bali.Methods: This research is quantitative, with data collection methods obtained through observation, interviews, and questionnaires. This study uses 50 respondents with the technique of proportional stratified random sampling. The data were analyzed using quantitative techniques, namely simple linear regression analysis.Results and discussion: The results of this study indicate that there is a negative and significant influence of workload on employee performance, and the magnitude of the effect of workload on employee performance is 31.1%. Along with hotel development in Bali, competition between accommodations to attract tourists is inevitable. One of the strategies used to win the match is providing quality services resulting from employee performance.Implication: In the Apurva Kempinski Bali, especially in the Front Office Department, employee performance is still not optimal because employees are laid off during the pandemic, which requires employees to work multitasking, which increases the workload of employees.